Analysis for Industrial Grid Containing Nonlinear Loads - Basim Mohammed Al Kadhimi (Wasit Journal of Engineering Sciences)
Harmonics is the most important issue among all issues related to the power quality. Harmonics comes from different non-linear loads like uninterruptible power supplies systems (UPS), variable speed motor drives, rectifiers, personal computers, adjustable speed drives, fluorescent lighting, rectifier banks, data processing loads, arc furnaces, and so on. Simulation of a real power supply system that consists of linear loads and nonlinear loads as variable speed drives has been carried out in the work. Variable speed drives generate harmonics into supply system that contains different values of compensated capacitors. Calculations of equivalent system reactance for generated harmonics, voltage harmonics, voltage harmonics in percentage, THD (Total Harmonic Distortion) of voltage, frequency characteristics, current flows in the system capacitor units have been worked out using Mathcad software. The obtained results have been compared with the European Standard (EN 50160) for supply quality requirements of the European Union.